Superior Labrum Injuries in Elite Gymnasts: Symptom, Pathology, and Outcome after Surgical Repair - Sugaya, Hiroyuki (Orthop J Sports Med, 2020)
OBJECTIVES: Superior labral anterior-posterior (SLAP) lesions are common among gymnasts and throwing athletes. Although SLAP lesions in throwers are well described in the literature, no study has described the characteristics of SLAP lesions in gymnasts. We aimed to reveal the characteristics of SLAP lesions in gymnasts by comparing the location and extension of these lesions between gymnasts and throwers. METHODS: This study included 27 shoulders in 20 male and 3 female patients with a mean age of 20 years (range, 16-25 years). We performed debridement alone for shoulders with a stable lesion. Anterior and/or posterior labrum repair was added for unstable SLAP lesions, depending on the extension and stability of the lesions. We investigated symptoms, onset, sports return based on patient records, and subjective shoulder values (SSVs). SLAP lesions were evaluated using the Snyder classification. The location and extension of SLAP lesions were determined from surgical records and videos, and described using the right shoulder clock-face method. During the same period, 65 baseball players (65 shoulders) underwent arthroscopic SLAP surgery. They were all men with a mean age of 23 years (range, 16-44 years). We also investigated the location and extension of SLAP lesions in baseball players for comparison. Statistical analysis was performed using the Mann-Whitney U-test for comparing the center and arc of SLAP lesions between gymnasts and baseball players. The Mann-Whitney U-test was also used to compare the preoperative and postoperative SSVs. The level of significance was set at P<0.05. RESULTS: Symptoms during gymnastics included pain (100%), apprehension (48%), or catching (11%). Twenty shoulders had symptom onset during gymnastics, most commonly during rings events. Type II SLAP lesions were found in 17 shoulders, type III in 2 shoulders, and type IV in 8 shoulders. The mean center of SLAP lesions was located at 11:40 in 27 gymnasts and at 10:40 in 65 baseball players, and the difference was statistically significant (P<0.001). The mean arc of SLAP lesions was 125° in gymnasts and 140° in baseball players, and the difference was not significant (P=0,09) (Figure 1). We performed debridement (Figure 2) in 2 shoulders (7%) and labrum repair (Figure 3,4) in 25 shoulders (93%). After surgery, all patients returned to gymnastics. The mean SSV was 35 (range, 10-90) preoperatively and 76 (range, 40-100) postoperatively. CONCLUSION: SLAP lesions in gymnasts were significantly located anteriorly than those in baseball players. Most SLAP lesions in the shoulders of gymnasts had symptom onset during suspension events such as rings or bars, and half of the gymnasts complained of shoulder apprehension in addition to pain. Fixation of both the anterior and posterior labrum was performed in 63% of the patients, and all patients returned to gymnastics after arthroscopic surgery. Secure repair of SLAP lesions may be important for good surgical outcomes because gymnasts require a stable glenohumeral joint.